WHAT IS THE MODEL OF MUSLIM RELATIONS WITH THE KAABA FROM THE PERSPECTIVE OF THE QUR'AN - Abulmajd, Abdurrahman (Universitas Muhammadiyah Surakarta, 2024)
The main idea of the research is to limit most of the connections that were linked to the Kaaba, the circumambulation connection or more severe, connections that were required by doctrine, and documented by traditional and rational inferences. The importance of the research lies in trying to cover most of the connections that were connected to the Kaaba, and to find out the nature and types of these connections, the bulk of their dimensions, and the strength of their cohesion. The problem of the research is represented by In the impact of these connections on the Muslim belief, the research aims to clarify these connections and arrange them in the appropriate model order, and provide fertile scientific material that deepens faith, refutes speculation, enriches objective knowledge, and creates a fertile background that gives the Muslim confidence when discussing with others about the Kaaba in particular, and thought. Islam in general, and the nature of the research required that I follow the descriptive, analytical, and deductive method, considering it to be the best method for the nature of the research. One of the most prominent findings reached by the researcher is that the connections associated with the Kaaba are diverse and can be limited to three main connections: divine connections, devotional connections, and security connections. And the connection of the Messenger of God, may God bless him and grant him peace, to the House is greater than that of Abraham, peace be upon him, because he, may God bless him and grant him peace, participated in building the House voluntarily and honorably - by the grace of God Almighty before the mission - and he re-placed the Black Stone. In its place, he decisively purified the house. On the day of the conquest, he purified it of idols, and purified it of the impurity of the polytheists in the Farewell Pilgrimage 10 AH, and he modified the circumambulation into an Irma and Sa’i. The Messenger of God, may God bless him and grant him peace, is the model to be followed in the rituals. Indeed, there is Amendments that Muhammad, may God bless him and grant him peace, wanted to make at home. Therefore, the researcher believes that looking at the connections associated with the Kaaba increases the believer’s strength and certainty, and that the connections may sometimes overlap, and that what the Messenger of God, may God bless him and grant him peace, did towards the House, exceeds what Abraham, peace be upon him, did.